Overview of the antimicrobial sensitivity pattern of the clinical isolates collected from patients at intensive care unit of a private hospital in Dhaka - Chakraborty, Prapti (BRAC University, 2018)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Microbiology, 2018.